Cissampelos pareira Linn: Natural Source of Potent Antiviral Activity against All Four Dengue Virus Serotypes. - Ruchi Sood; Rajendra Raut; Poornima Tyagi; Pawan Kumar Pareek; Tarani Kanta Barman; Smita Singhal; Raj Kumar Shirumalla; Vijay Kanoje; Ramesh Subbarayan; Ravisankar Rajerethinam; Navin Sharma; Anil Kanaujia; et al. (PLoS Neglected Tropical Diseases, 2015)
Background Dengue, a mosquito-borne viral disease, poses a significant global public health risk. In tropical countries such as India where periodic dengue outbreaks can be correlated to the high prevalence of the mosquito vector, circulation of all four dengue viruses (DENVs) and the high population density, a drug for dengue is being increasingly recognized as an unmet public health need. Methodology/principal findings Using the knowledge of traditional Indian medicine, Ayurveda, we developed a systematic bioassay-guided screening approach to explore the indigenous herbal bio-resource to identify plants with pan-DENV inhibitory activity. Our results show that the alcoholic extract of Cissampelos pariera Linn (Cipa extract) was a potent inhibitor of all four DENVs in cell-based assays, assessed in terms of viral NS1 antigen secretion using ELISA, as well as viral replication, based on plaque assays. Virus yield reduction assays showed that Cipa extract could decrease viral titers by an order of magnitude. The extract conferred statistically significant protection against DENV infection using the AG129 mouse model. A preliminary evaluation of the clinical relevance of Cipa extract showed that it had no adverse effects on platelet counts and RBC viability. In addition to inherent antipyretic activity in Wistar rats, it possessed the ability to down-regulate the production of TNF-α, a cytokine implicated in severe dengue disease. Importantly, it showed no evidence of toxicity in Wistar rats, when administered at doses as high as 2g/Kg body weight for up to 1 week. Conclusions/significance Our findings above, taken in the context of the human safety of Cipa, based on its use in Indian traditional medicine, warrant further work to explore Cipa as a source for the development of an inexpensive herbal formulation for dengue therapy. This may be of practical relevance to a dengue-endemic resource-poor country such as India.